Gender neutral toilet standards guideline recommendations based on Indonesian behavior and habits - Melsa Rayan Sari; Ridwan Setia Permana; Mohamad Otto Ridwan Mandagi; Citra Tifany Fahira; Satria Eko Wicaksono; Hana Faza Surya (Universitas Indraprasta PGRI, 2024)
The availability of public toilets in public spaces is essential because sanitation is one of the basic human needs. Mall is one of the places visited by various groups of people, therefore the design of public toilets in mall need to consider the needs of diverse toilet users. In Indonesia, toilet design guidelines are already made by the Indonesian Toilet Association, but they have yet to pay attention to all the inclusivity points of some groups. Good public facilities should be able to meet the sanitation needs of all users, including people with disabilities, unconventional gender groups (transgender and non-binary), and companions for children/parents of different genders. Data were collected through observation, questionnaires, interviews, and literature studies. Observation were carried through three shopping mall in bandung, braga citywalk, bandung beautiful plaza, paris van java to observe the existing toilet conditions. Descriptive and experimental qualitative methods carry out the method of data analysis. A comparative study was conducted on existing toilet design guidelines to formulate points of recommendations for designing gender-neutral toilets that are tailored to the behavior of the Indonesian people, followed by an experimental process to produce visual recommendations for gender-neutral toilet designs, namely single-stalled, multi-stalled, enclosed, and multi-stalled open space toilet types.